Extension of direct strength method to two dimensional cold formed steel frame - Kubde, P. W.; Sangle, K. K. (Revista ALCONPAT, 2017)
The use of cold-formed marco de acero (CFS) structures is increasing due to the advances in manufacturing, construction technologies and relevant standards. CFS has many advantages. However, the design of CFS structures is complex because of their thin walled open sections making them vulnerable to torsional-flexural buckling and local buckling. Direct strength method (DSM) is the method available for individual beam and column, with certain limitations. To overcome one such limitation this paper attempts to find a formula as an extension to DSM. Already experimented frame was used to validate software model and same frame with different heights was analysed by Finite Element Method and DSM and a formula is obtained as an extension to DSM. Keywords: cold formed marco de acero; distortional buckling; global buckling; direct strength method; finite element analysis.